Thermogravimetric kinetics of catalytic and non-catalytic pyrolytic conversion of palm kernel shell with acid treated coal bottom ash - Patrick, D.O. (Institute of Physics Publishing, 2020)
The catalytic and non-catalytic pyrolytic conversion kinetics of palm kernel shell with untreated (as received) and H2SO4 treated coal bottom ash as catalyst were investigated in this study. The activation energy was determined using Flynn-Wall-Ozawa (FWO) kinetic model and distributed activation energy model (DEAM) isoconversional kinetic models. The study was conducted using thermogravimetric analysis at 10, 20, 30 and 50 Â°C/min heating rates. The activation energy (Ea) ranged from 145.7-228.3 kJ/mol and 142.1-274.2 kJ/mol for FWO and DEAM, respectively. The use of acid treated ash reduced the activation energy compared to the non-catalytic process while the untreated ash increased the activation energy. Â© Published under licence by IOP Publishing Ltd.